RELEVANSI DAN KEKUATAN HUKUM AKTA PERDAMAIAN DALAM PENYELESAIAN SENGKETA DI BIDANG EKONOMI - Rilda Murniati (Fiat Justisia: Jurnal Ilmu Hukum, 2015)
Business relationships can give rise to disagreements that need to be resolved through the procedures for handling civil cases. In practice to solve business problems, the parties can make a peace agreement in the form of a deed under hand or a notarial deed known as a deed of peace. Mediation is a part of the stage of completion of a court that is required is offered by the judges and may terminate the proceedings if it obtained an agreement in mediation by the litigants. However, to simplify the process of resolving civil cases the parties can make advance a peace agreement in the form of a deed under hand or a notarial deed. Furthermore, the deed of peace created in front of the notary, submitted to the court to obtain a determination of the judges to get legal certainty.Keywords: The Power of Law, Deed of Peace, Dispute Resolution